Identification of Three Novel Genes in Phenuiviridae Detected from Aedes Mosquitoes in Hokkaido, Japan - Uchida, Leo; Sakurai, Yoshimi; Shimooka, Makoto; Morales-Vargas, Ronald Enrique; Hagiwara, Katsuro; Muramatsu, Yasukazu (Japanese Journal of Infectious Diseases, 2023)
Mosquitoes are important arthropod vectors of arboviruses. The family Phenuiviridae includes several medically important arboviruses, such as the Rift Valley fever phlebovirus and Toscana phlebovirus. Recent comprehensive genetic analyses have identified many novel mosquito-specific viruses that are phylogenetically related to Phenuiviridae. We collected mosquitoes from Hokkaido in northern Japan, and conducted reverse transcription polymerase chain reactions (RT-PCRs) targeting the RNA-dependent RNA polymerase (RdRp) gene of Phenuiviridae. A total of 285 pools, comprising 3,082 mosquitoes from 2 genera and 8 species, were collected. Partial RdRp sequences were detected in 97 pools, which allowed us to classify the viruses into 3 clusters provisionally designated as Etutanne virus (ETTV) 1, 2, and 3. The virus most closely related to ETTVs is Narangue virus (family Phenuiviridae, genus Mobuvirus), which was detected in Mansonia mosquitoes; the nucleotide and amino acid sequences of the Narangue virus are 58.4–66.2% and 64.7–86.7% similar, respectively, to those of ETTVs. PCR and RT-PCR using DNA and RNase digestion methods showed that the ETTVs are RNA viruses that do not form non-retroviral integrated RNA virus sequences in the mosquito genome.